Lending Cycles and Real Outcomes: Costs of Political Misalignment - Cagatay Bircan; Orkun Saka (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We document a strong political cycle in bank credit and industry outcomes in Turkey. In line with theories of tactical redistribution, state-owned banks systematically adjust their lending around local elections compared with private banks in the same province based on electoral competition and political alignment of incumbent mayors. This effect only exists in corporate lending and creates credit constraints for firms in opposition areas, which suffer drops in assets, employment and sales but not firm entry. Financial resources and factors of production are misallocated as more effient provinces and industries suffer the greatest constraints, reducing aggregate productivity.
Keywords: G21; D72; D73; P16; 330; bank credit; electoral cycle; state-owned banks; misallocation